HADITH-BASED FAMILY RESILIENCE IN FATHERLESS CONTEXTS: AN INTEGRATIVE CONCEPTUAL MODEL - Khaerun Nisa Nuur; Huzaifah Dwi Aryani (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines fatherless families beyond a deficit-oriented perspective by proposing a resilience-based framework grounded in Prophetic traditions (hadith). It addresses the gap between risk-focused psychological studies and normative Islamic discourse by developing a conceptual model that explains how families adapt in the absence of paternal involvement. A qualitative design was employed through an integrative literature review combined with thematic analysis. Primary data consisted of selected hadith related to caregiving, responsibility, and social relations, while secondary sources included contemporary studies on fatherlessness and family resilience. The analysis followed iterative processes of coding, categorization, and conceptual synthesis. The study identifies four interrelated pillars of resilience: tauhid-oriented spirituality as a system of meaning-making, structural flexibility through role redistribution, social support as a buffering mechanism, and individual autonomy as an internal adaptive capacity. These dimensions operate systemically, indicating that resilience is shaped not by structural completeness but by the family’s ability to reorganize meaning, roles, and relational resources. The findings are derived from a conceptual framework based on textual analysis and have not yet been empirically validated. Future research is needed to test the model across diverse socio-cultural contexts using empirical and longitudinal approaches. This study offers an integrative contribution by bridging contemporary resilience theory with hadith-based perspectives, resulting in a theoretically grounded and contextually relevant model for understanding family resilience in Muslim settings.